The Representation of Ethnic Identity in Banjar Fiction by Jamal T. Suryanata - Lismayanti, Heppy; Arifin, Johan; Kamariah, Kamariah (LPPPIPublishing, 2024)
This study aims to analyze the representation of ethnic identity in Banjar fiction by Jamal T. Suryanata. Banjar fiction, as part of regional literature, plays an important role in depicting the life, culture, and thoughts of the Banjar community. The main objective of this research is to identify how Banjar ethnic identity is portrayed in Suryanata's works, as well as to understand how the characters, themes, and symbols used in these works reflect the social and cultural construction of Banjar ethnicity. The method used in this study is descriptive qualitative text analysis. This research examines several works of Banjar fiction by Jamal T. Suryanata, such as novels and short stories, through an ethnic identity theory approach and literary sociology studies. The analysis focuses on the characters in the stories, cultural depictions, and the role of the Banjar language in shaping the image and characteristics of ethnicity in these works. The findings of this study indicate that Banjar ethnic identity in Jamal T. Suryanata’s works is portrayed through depictions of daily life, customary values, and the social conflicts faced by the Banjar community. The characters in these fictions often experience shifts or quests for identity, both in relation to other communities and in maintaining their original culture. The Banjar language also plays an important role in reinforcing the authenticity and depth of the representation of Banjar cultural identity. Themes such as unity, social change, and modernization challenges become central issues that highlight the dynamics of ethnic identity. The implications of this research show that Banjar literature functions not only as entertainment but also as a medium for communicating and preserving cultural identity. The representation of ethnic identity in Banjar fiction contributes to a deeper understanding of Banjar cultural values and how its community faces the challenges of modern times. This study also opens up space for further research on the role of regional literature in preserving Indonesia’s cultural diversity.